2017
DOI: 10.1016/j.tox.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Butadiene-induced mitochondrial dysfunction is correlated with mitochondrial CYP2E1 activity in Collaborative Cross mice

Abstract: Cytochrome P450 2E1 (CYP2E1) metabolizes low molecular weight hydrophobic compounds, including 1,3-butadiene, which is converted by CYP2E1 to electrophilic epoxide metabolites that covalently modify cellular proteins and DNA. Previous CYP2E1 studies have mainly focused on the enzyme localized in the endoplasmic reticulum (erCYP2E1); however, active CYP2E1 also localizes in mitochondria (mtCYP2E1) and the distribution of CYP2E1 between organelles can influence an individual's response to exposure. Relatively fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The metabolites have been shown to modify cellular DNA and result in genotoxicity; however, the possibility of mitochondrial dysfunction had not been explored. We have recently shown that genetically diverse mice exposed to a high dose of inhaled butadiene exhibit impaired mitochondrial complex activities in complexes I, II, and IV and that impairment is correlated with increased CYP2E1 activity in mitochondria 92 . This finding demonstrates a link between mtCYP2E1 activation of butadiene and exposure-induced mitochondrial dysfunction, although its relevance in toxicity of environmental exposures to butadiene remains to be explored.…”
Section: Exogenous Substrates Of Cyp2e1 That Damage Mitochondriamentioning
confidence: 99%
“…The metabolites have been shown to modify cellular DNA and result in genotoxicity; however, the possibility of mitochondrial dysfunction had not been explored. We have recently shown that genetically diverse mice exposed to a high dose of inhaled butadiene exhibit impaired mitochondrial complex activities in complexes I, II, and IV and that impairment is correlated with increased CYP2E1 activity in mitochondria 92 . This finding demonstrates a link between mtCYP2E1 activation of butadiene and exposure-induced mitochondrial dysfunction, although its relevance in toxicity of environmental exposures to butadiene remains to be explored.…”
Section: Exogenous Substrates Of Cyp2e1 That Damage Mitochondriamentioning
confidence: 99%
“…Two inbred mouse strains, C57BL/6J and CAST/EiJ, have been extensively studied based on their sensitivity and resistance to 1,3-butadiene-induced DNA damage (Koturbash et al 2011). In addition, inter-strain variability has also been identified in 1,3-butadiene-induced mitochondrial dysfunction using the Collaborative Cross mouse population model (Hartman et al 2017). With respect to carcinogenesis-related genetic and epigenetic effects of 1,3butadiene in mice, it was found that while exposure-induced DNA adducts are present in lung, liver, and kidney (Israel et al 2018), epigenetic alterations (Chappell et al 2014) and tumor formation are restricted to the liver and lung (Melnick et al 1992;National Toxicology Program 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Subcellular fractionation from liver, heart, and brain soft tissue was carried out as previously described for mammalian liver(Hartman et al, 2017). Briefly, tissues were homogenized in buffer containing 2.5mM MOPS, pH 7.4, 2mM EDTA, 70mM sucrose, and 220mM mannitol and pulverized using a 2mL Tenbroeck tissue grinder.…”
Section: Methodsmentioning
confidence: 99%